ETNOPEDAGOGI DIGITAL: REAKTUALISASI KEARIFAN LOKAL KABUPATEN MERANGIN-JAMBI MELALUI GAME EDUKASI BERBASIS KEBUDAYAAN DI KELAS IV SD - Hopipah, Ria; Mutia Nurhamida; Yanti; Sindi; Hasri Agung Zulha; Mona Ariesta; Pebby Olla Yolanda; Mila Amelia; Ficri Amrullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The massive wave of global modernization and digitalization threatens the existence of local wisdom values among the younger generation, including elementary school students in Merangin Regency, Jambi. Digital ethnopedagogy emerges as an alternative paradigm to integrate local cultural heritage with technological innovation. This study aims to develop, test the validity, practicality, and effectiveness of an educational game based on the "Merangin Geopark Adventure" to improve the understanding of local wisdom and patriotism among fourth-grade elementary school students. This study employed a Research and Development (R&D) method using the ADDIE model combined with a quasi-experimental design. The trial subjects involved 72 fourth-grade students from two elementary schools in Merangin Regency. Data were collected through expert validation sheets, teacher and student response questionnaires, and a local wisdom understanding test. The results of media and material expert validation showed that the educational game was categorized as "Highly Eligible" (91% and 93%). The practicality test by teachers and students achieved a percentage of 89.5%. Furthermore, the results of the quasi-experimental test using the Independent Samples T-Test demonstrated a highly significant increase in local wisdom understanding in the experimental group using the educational game (M = 86.4; SD = 5.4) compared to the control group using the conventional approach (M = 71.2; SD = 6.9) with p < 0.001. These findings confirm that the reactualization of local wisdom, such as the Merangin Geopark, oral traditions, and local customs through interactive digital platforms can improve cognitive efficiency and strengthen students' cultural retention from an early age.